2021
DOI: 10.3390/molecules26237147
|View full text |Cite
|
Sign up to set email alerts
|

On the Question of Zwitterionic Intermediates in the [3 + 2] Cycloaddition Reactions between C-arylnitrones and Perfluoro 2-Methylpent-2-ene

Abstract: The molecular mechanism of the [3 + 2] cycloaddition reaction between C-arylnitrones and perfluoro 2-methylpent-2-ene was explored on the basis of DFT calculations. It was found that despite the polar nature of the intermolecular interactions, as well as the presence of fluorine atoms near the reaction centers, all reactions considered cycloaddition proceed via a one-step mechanism. All attempts for the localization of zwitterionic intermediates on the reaction paths were not successful. Similar results were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This Special Issue (SI) focuses on Huisgen 3 + n dipolar cycloaddition reactions as a useful and powerful tool in the synthesis and chemistry of new heterocycle derivatives. The SI provides an update of relevant and important original contributions [1,2,[4][5][6][7][8] and reviews [3,9] pertaining to these reactions, which have brought about significant advances in the development of the field of heterocycle derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue (SI) focuses on Huisgen 3 + n dipolar cycloaddition reactions as a useful and powerful tool in the synthesis and chemistry of new heterocycle derivatives. The SI provides an update of relevant and important original contributions [1,2,[4][5][6][7][8] and reviews [3,9] pertaining to these reactions, which have brought about significant advances in the development of the field of heterocycle derivatives.…”
mentioning
confidence: 99%
“…The first original contribution to the SI is focused on the zwitterionic intermediates in the [3 + 2] cycloaddition reactions between C-arylnitrones (1,3-dipol) and perfluoro 2-methylpent-2-ene as a dipolarophile [4]. As for its mechanisms, DFT calculations have revealed that the [3 + 2] cycloaddition reactions occur via a one-step mechanism, irrespective of the nature of the reactants.…”
mentioning
confidence: 99%